(untitled) (International Journal of Engineering and Computer Science, 2014)
Radio Frequency Identification (RFID) has attracted considerable attentions in recent years for its broad applications and complements to the current GPS navigation system when GPS signals are not available (such as in tunnels) or if the GPS position is ambiguous to a vehicle (such as at cloverleaf intersections). But in practice, GPS does not provide sufficient information for navigation due to its low positioning accuracy (5 to 7 meters).Moreover, even combined with map-matching technologies, GPS still cannot achieve lane level positioning and cannot provide information regarding the traffic direction in the current lane. In this paper we use ARM based LPC2148, S3C2440A, PIC18F452, RF434, ZIGBEE, RFID READER. The proposed system contains mainly four nodes vehicle unit, two reader units, central unit. Vehicle unit is implemented on ARM7, Central unit on ARM9. The reader Units is placed in a distance of 50-100 mts to each. When a vehicle crosses first reader unit the tag attached to vehicle read by the reader unit and it starts timer send intimation to central station , when the vehicle reaches the second Reader unit there also the Tag is read by reader unit and it also send the intimation and time details to central station. By taking these details the central station calculates the speed of the vehicle and also detects the location of vehicle based on reader’s position and sends this information to Vehicle. If the vehicle is going with high speed than predefined then the speed control unit slowly reduce the vehicle speed. The central unit also provides the next location information to vehicle so that he can decide the route that he wants to go. The communication between Vehicle unit and Central unit is using ZigBee whereas the communication between reader units and Central unit is using RF434 wireless module